The dawn of urbanity - Lidia Decandia; Natalia Agati (City, Territory and Architecture)
Abstract Contemporary urban transformations are increasingly challenging the traditional categories through which the urban has been conceptualized, highlighting the need for a critical reinterpretation of its origins. Western urbanity has been, in fact, structured around the dichotomy between nature and culture, identifying the city’s origin as a centralised and hierarchically organized space, a place of power consolidation and surplus accumulation. This study seeks to deconstructs this dominant and monolithic narrative, exploring the hypothesis that urbanity may have first emerged within sacred places, through ritual practices and festive gatherings. Drawing on the analysis of prehistoric sites such as the Palaeolithic caves, and later megalithic complexes like Göbekli Tepe and Stonehenge, the research shows how these auroral places functioned as social magnets, temporary nodes of aggregation where diverse and territorially dispersed communities would come together to celebrate collective being, consolidate bonds and share symbolic systems and foundational narratives. This perspective challenges the dualistic and economistic interpretation of the city as a mere tool for territorial control and economic productivity. Instead, it suggests that early forms of urbanity originated from the human need to construct shared meanings through aesthetic, convivial and ritual practices. Moreover, through an exemplary case study—the ceremonial sites of central Sardinia—the article demonstrates how this mode of inhabiting space has persisted in certain cultures up to the near-contemporary period, revealing that urbanity itself is not a fixed, naturalized or universal form, but rather one that can be expressed through diverse spatial and cultural articulations. Retracing this trajectory not only helps to destabilize ingrained conception of the city, but also offers tools for rethinking the present and imagining new futures for contemporary urbanities. By acknowledging and valorising the forms of inhabitation that emerge on the peripheries of dominant spatial regimes—within marginal territories and through aesthetic and political practices of spacial reappropriation—this study contributes to a more plural and situated understanding of the urban present and future conditions.